2018
DOI: 10.1038/s41578-018-0026-7
|View full text |Cite
|
Sign up to set email alerts
|

Point defect engineering in thin-film solar cells

Abstract: Control of defect processes in photovoltaic materials is essential for realising high-efficiency solar cells and related optoelectronic devices. The concentrations of native defects and extrinsic dopants tune the Fermi level and enable semiconducting p-n junctions; however, fundamental limits to doping exist in many compounds. Optical transitions involving defect states can enhance photocurrent generation through sub-bandgap absorption; however, such states are often responsible for carrier trapping and non-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
274
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 346 publications
(281 citation statements)
references
References 258 publications
(304 reference statements)
2
274
0
5
Order By: Relevance
“…As the fundamental origin, structural defects, and impurities in semiconductor materials play an important role in the overall performance of electronic devices in general . In several photovoltaic technologies (e.g., Si, CIGS, CdTe), the presence of electronic defects within the semiconductor band gap limits the efficiency, reproducibility, as well as stability/lifetime . Therefore, efforts have been made in the direction to minimize the defect density by well‐controlled semiconductor fabrication technology.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As the fundamental origin, structural defects, and impurities in semiconductor materials play an important role in the overall performance of electronic devices in general . In several photovoltaic technologies (e.g., Si, CIGS, CdTe), the presence of electronic defects within the semiconductor band gap limits the efficiency, reproducibility, as well as stability/lifetime . Therefore, efforts have been made in the direction to minimize the defect density by well‐controlled semiconductor fabrication technology.…”
Section: Discussionmentioning
confidence: 99%
“…4) The fourth functionality is associated with the enlargement in grain size induced by the thiol groups. The growth of monolithic‐type and/or large perovskite grains in polycrystalline films is a widely employed strategy to reduce detrimental defects . Although several groups have reported that amino‐functionalized groups are efficient for passivating under‐coordinated PbI 6 octahedra (Table S2), Xu et al .…”
Section: Defect Passivation In Metal Halide Perovskitesmentioning
confidence: 99%
See 2 more Smart Citations
“…[1] In this pursuit, the incorporation of intrinsic or extrinsic atomic defects in structures that either exhibit naturally occurring vacancies or those with synthetically or postsynthetically introduced vacancies has been established as ap owerful approacht ot he finetuning of the properties of aw ide range of functional materials. Many of today's prominentm aterials, such as high-transition-temperature superconductors, [2,3] solar-drivenp hotocatalysts, [4][5][6][7] photovoltaic materials, [8] metal-organic frame-works, [9][10][11] and ferroelectrics, [12][13][14] are imperfect systems with defect-induced, locally broken periodic structures,i nw hich imperfection plays ap ivotal role in governing, or at least affecting, their physiochemicalproperties. [15][16][17][18][19][20] Materials consisting of as equence of infinitely repeating stacksof[Bi 2 O 2 ] 2 + layers,such as bismuth-based cupratesuperconductors, bismuth oxyhalides, and Aurivillius phases, have attracted intensivea ttention because they exhibit an array of tantalizing properties, such as superconductivity,p hotocatalytic, photoluminescence (PL),a nd ferroelectricity.…”
Section: Introductionmentioning
confidence: 99%